Membangkitkan UMKM Kerupuk Singkong Desa Tonggorisa Di Masa Pendemi Covid19 Melalui Sosialisasi Digital Marketing Dan Inovasi Produk Untuk Meningkatkan Pendapatan - Muhamad Rimawan (Edumedia Solution, 2022)
Various problems related to the decline in the MSME economy during the current COVID-19 pandemic have had a significant impact on MSME actors. One of the MSMEs affected by the pandemic is an SME that makes cassava crackers in Tonggorisa Village, Palibelo District, Bima Regency, which has experienced a decline in income. Dozens of people get income from producing these crackers. To stabilize sales and people's income, we help by providing socialization and training involving Digital Marketing and product innovation. In the first stage, we disseminated the importance of doing business during the Covid-19 pandemic, aimed at the impacted community MSMEs must continue to run and be stable as before the pandemic. In the second stage, we introduce digital marketing to the public so that it can be used as a medium to market crackers to a wider market. It is hoped that with this socialization, the community can transform to digital business to get more income potential. In the last stage, we explain the importance of product innovation. We explain the importance of product innovation so that there is product diversification that can attract consumer interest so that they can survive in the midst of competition in the digital business. It is hoped that with this socialization, cassava crackers SMEs can increase their income and survive in the midst of a pandemic.